The indicator of clinical outcomes for patients with heterotopic pregnancy following in-vitro fertilization with embryo transfer - Jianhong Shang; Ruan Peng; Ju Zheng; Meifang Lin (Elsevier, 2019)
Objective: To explore the early predictors for pregnancy outcomes in patients with heterotopic pregnancy (HP) following in-vitro fertilization with embryo transfer (IVF-ET). Material and methods: This retrospective study reviewed 81 patients with HP following IVF-ET in our institution between January 2003 and September 2017. The relationships between clinical outcomes and general characteristics, sonographic features and different management options were analyzed by logistic regression analysis. Results: The gestational age at the time of diagnosis was 50.9 ± 12.3 days. Among these cases, 76 were accurately diagnosed by TVS, 1 was misdiagnosed as adnexal torsion by TVS, and 4 were confirmed to have IUPs after the surgical treatment. Hence, the sensitivity of TVS for detecting HP was 93.8% (76/81). However, forty-seven patients (58.0%) had suspected HP when they underwent the initial TVS. Among these patients, live births occurred for 60 patients, 11 of whom delivered preterm. The miscarriage rate was 58.3% (14/24) for patients without IUP cardiac activity at HP diagnosis, and 12.3% (7/57) for patients with IUP cardiac activity; a significant correlation was identified (χ2 = 18.651, P < 0.001). Additionally, the abortion rate of patients following fresh non-donor embryo was higher than patients after frozen-thawed embryo (χ2 = 10.437, P = 0.001). Further by logistic regression analysis, patients following frozen-thawed embryo and an IUP with cardiac activity at HP diagnosis were identified as two independent factors of pregnancy outcome. (OR = 0.060, 95%CI = 0.008-0.471, P = 0.007; OR = 0.010, 95%CI = 0.001-0.124, P<0.001). Conclusions: Patients following frozen-thawed embryo and an IUP with cardiac activity at HP diagnosis could be the independent predictors for a favorable prognosis. Keywords: Independent predictor, Clinical outcomes, Heterotopic pregnancy, Transvaginal sonography